Answer:
x = -45, y = -40
Step-by-step explanation:
Based on the first clue, we find out that
x + 5 = y
5x = 6y + 15
We can re-write the first equation to x = y - 5.
Therefore, the second equation can also be written as 5(y - 5) = 6y + 15
This can be simplified to 5y - 25 = 6y + 15
We can subtract 6y from each side, and add 25 to each side;
5y - 6y = 15 + 25
Therefore, -y = 40
Therefore y = -40.
Now let's plug this back into the original equation, to get : x + 5 = -40
x=-45
Answer:
6^-1
Step-by-step explanation:
6^-6 - (-5) = 6^(-6 + 5) = 6^(-1)
A lot of things are going on in this question. Notice how the 5 is handled. It starts off in the denominator as - 5 and when brought to the numerator it becomes -(-5) which makes it + 5.
The answer is then easy. It is 6^(-6 + 5) = 6^-1
You could give the answer as 1/6 but that is not what the question says.
Answer:
3
Step-by-step explanation:
distance formula
Well the first equation has a variable in it while the other one doesn't also the first expression if set equal to 0 is -2 while the other one is 5